2003
DOI: 10.1046/j.1365-2516.2003.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical, reproductive and psychosocial experiences of women diagnosed with von Willebrand's disease receiving care in haemophilia treatment centres: a case–control study

Abstract: Women with VWD experience menorrhagia and other gynaecological conditions at a higher frequency than women without bleeding disorders. Menstruation in women with VWD has a negative impact on life activities. The prevalence of depression was not elevated in this group of women whose VWD is being managed in an HTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 13 publications
(12 reference statements)
4
171
0
3
Order By: Relevance
“…These results were concordant with those of previous studies, which demonstrated that a higher number of women with VWD compared with women in the general population perceived limitations in their overall life activities due to menstruation (12,29). Kirtava et al (12) performed a case control study on 62 women with VWD and demonstrated that 23 (32.1%) of these women perceived menstrual bleeding to limit their overall life activities and negatively affect their lives. Among the 70 controls of the study, only 7 women (10.0%) perceived limitations (12).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results were concordant with those of previous studies, which demonstrated that a higher number of women with VWD compared with women in the general population perceived limitations in their overall life activities due to menstruation (12,29). Kirtava et al (12) performed a case control study on 62 women with VWD and demonstrated that 23 (32.1%) of these women perceived menstrual bleeding to limit their overall life activities and negatively affect their lives. Among the 70 controls of the study, only 7 women (10.0%) perceived limitations (12).…”
Section: Discussionsupporting
confidence: 90%
“…Kirtava et al (12) performed a case control study on 62 women with VWD and demonstrated that 23 (32.1%) of these women perceived menstrual bleeding to limit their overall life activities and negatively affect their lives. Among the 70 controls of the study, only 7 women (10.0%) perceived limitations (12). A study performed by Rae et al (29) concluded that among 84 women with inherited bleeding disorders and HMB, the majority (77.5%) reported that menstrual bleeding interfered with daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The majority (74-95%) of women with known VWD report menorrhagia. [13][14][15][16] Menorrhagia has also been reported in 50-60% of women with rarer factor deficiencies. 14,17 Women with IBDs also suffer from prolonged menstruation.…”
Section: Menorrhagia and Ibdsmentioning
confidence: 99%
“…59,60 Other gynaecological problems A survey of 102 women with VWD showed a higher prevalence of pelvic pathology in women with IBDs compared to controls, including endometriosis (30% vs 13%) endometrial hyperplasia (10% vs 1%), fibroids (32% vs 17%) and endometrial polyps (8% vs 1%). 16 It is doubtful that women with IBDs are more likely to develop these pathologies, but as these conditions often present with bleeding, women with IBDs are more likely to be symptomatic. 35 Further studies are required to assess the prevalence and severity of these gynaecological conditions in women with IBDs.…”
Section: Haemorrhagic Ovarian Cystsmentioning
confidence: 99%